2008
DOI: 10.1007/s11101-008-9111-7
|View full text |Cite
|
Sign up to set email alerts
|

Indolic glucosinolates at the crossroads of tryptophan metabolism

Abstract: In plants the amino acid tryptophan (Trp) is used to synthesize proteins and a wide variety of compounds that control development and defense. Recent studies in the reference plant Arabidopsis thaliana have elucidated a number of tryptophan secondary metabolism pathways derived from the Trp metabolite, indole-3-acetaldoxime (IAOx), particularly the pathway for synthesis of indolic glucosinolate (IG) herbivory defense compounds. Analyses of mutants, natural variants, and transgenic strains with perturbations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 70 publications
0
31
0
1
Order By: Relevance
“…A priori, this seemed a very unlikely scenario, because the CYP79B2/B3 pathway is known to operate mainly in Brassica spp. (Bender and Celenza, 2009;Sugawara et al, 2009), whereas auxin biosynthesis via YUCs has also been demonstrated in species beyond this genus (Tobeñ a-Santamaria et al, 2002;Gallavotti et al, 2008). Nevertheless, the relationship between these two pathways may not be as clear as one may have anticipated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A priori, this seemed a very unlikely scenario, because the CYP79B2/B3 pathway is known to operate mainly in Brassica spp. (Bender and Celenza, 2009;Sugawara et al, 2009), whereas auxin biosynthesis via YUCs has also been demonstrated in species beyond this genus (Tobeñ a-Santamaria et al, 2002;Gallavotti et al, 2008). Nevertheless, the relationship between these two pathways may not be as clear as one may have anticipated.…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis thaliana, IAOx is produced from Trp by a duo of highly related cytochrome P450s, CYP79B2 and CYP79B3 (Zhao et al, 2002;Sugawara et al, 2009). The bulk of IAOx produced is typically used in the synthesis of defense compounds, such as indole glucosinolates and camalexins (Glawischnig et al, 2004;Bender and Celenza, 2009). Under standard growth conditions, IAOx can also be converted to IAA via at least two intermediates, IAM and indole-3-acetonitrile (IAN) (Sugawara et al, 2009); however, this route is not believed to be a major source of IAA during normal plant development.…”
Section: Introductionmentioning
confidence: 99%
“…IGs are an important sink for Trp in Arabidopsis, and mutants with reduced IGs display increased sensitivity to 5MT (Celenza et al 2005;Bender and Celenza 2009). The iss1-1 mutant had similar IG levels to WT whether grown on PNS or PNS + indole media, indicating that conversion of Trp to IGs is not altered in the iss1-1 mutant.…”
Section: Iss1-1 Makes Normal Levels Of Indolic Glucosinolatesmentioning
confidence: 99%
“…2). From mutant analysis, it appears that indolic secondary metabolites such as IGs and camalexin are a major metabolic sink for Trp (Bender and Celenza 2009). IAOx can be diverted to IAA synthesis from pathways that (a) primarily function in defense against biotic stress (Hull et al 2000;Zhao et al 2002;Bednarek et al 2009;Clay et al 2009;Mikkelsen et al 2009), and (b) are not ubiquitous in the plant kingdom (Sugawara et al 2009).…”
Section: Progress In Filling In the Gaps For Multiple Biosynthetic Romentioning
confidence: 99%
“…Additionally, there may be separate IAOx pools in IGproducing plants. IAOx destined for IG synthesis is derived from the CYP79B2 and CYP79B3 pathway, and if IAOx is also derived from YUCCA, it does not contribute to IG synthesis (reviewed in Bender and Celenza 2009 (Sugawara et al 2009). Label from IAOx was incorporated into both IAN and IAM, but to different degrees, seeming to rule out a precursor product relationship between IAN and IAM.…”
Section: Progress In Filling In the Gaps For Multiple Biosynthetic Romentioning
confidence: 99%